Tổng hợp và khảo sát tính chất quang của các hạt nano vàng dạng cầu định hướng ứng dụng trong y sinh. - Liên, Nghiêm Thị Hà; Hải, Nguyễn Thanh; Hoà, Vũ Xuân; Hoà, Đỗ Quang; Nhung, Trần Hồng (Vietnam Journal of Chemistry, 2012)
The colloidal nanosize golds were synthesized from metal precursor chloroauric acid (HAuCl4) using trisodium citrate dehydrate (C6H5O7Na3) as reducing and stabilizing agents. The optical properties of colloidal gold solution have been investigated under the different synthetic conditions and aging time. The results show that the absorption and the stability of the colloidal gold nanoparticles depend robustly on the synthetic conditions and pH of media.